Biopolymeric antimicrobial films: Study of the influence of hydroxypropyl methylcellulose, tapioca starch and glycerol contents on physical properties - Espinel Villacrés, Ricardo Alexander (2014)
Mixture design methodology was applied to study the effect of different levels of tapioca starch (TS), hydroxypropyl methylcelullose (HPMC), and glycerol (Gly) on the physical properties of biopolymeric films supporting potassium sorbate (KS; 0.3% w/w) with the goal of contributing to the development of materials for preventing food surface contamination. Mechanical properties, water vapour permeability (WVP), solubility in water (S) and colour attributes were evaluated on the films. HPMC addition produced an increase of elastic modulus (Ec), stress at break (σb) and S. It also decreased the yellow index (YI) values and the strain at break (εb). The study was deepened using the formulation containing 2.67 g/100 g of TS, 0.67 g/100 g of HPMC, 1.67 g/100 g Gly and 0.3 g/100 g KS, observing that it behaved as an effective antimicrobial barrier against Zygosaccharomyces bailii external contamination. Microstructural analysis allowed us to conclude that HPMC incorporation to a TS network decreased roughness of the films and it also increased permeability to oxygen (PO 2).